Complexity of Damage-Associated Molecular Pattern Molecule Expression Profile in Porcine Brain Affected by Ischemic Stroke - Golubczyk, Dominika; Mowinska, Aleksandra; Holak, Piotr; Walczak, Piotr; Janowski, Miroslaw; Malysz-Cymborska, Izabela (International journal of molecular sciences, 2025)
Studies using large animal models are essential for better understanding the molecular processes underlying neurological diseases, including ischemic stroke, and serve as a robust foundation for evaluating potential therapies. To better understand the complex role of damage-associated molecular pattern molecules (DAMPs) after ischemia, we aimed to determine their expression in the porcine brain affected by ischemic stroke at four time points: 6 h, 24 h, 3 days and 7 days post-stroke. Within the first 24 h after the stroke, we observed the increased expression of several key factors, including calcium-binding proteins, peroxiredoxins, heat shock proteins and interleukins (1α and 1β, IL10, IL17α). Moreover, by day 7, multiple DAMPs were up-regulated, coinciding with an enhanced expression of vascular endothelial growth factor A (VEGFA) in the affected hemisphere. The effects of ischemic stroke were also evident systemically, as indicated by the altered serum levels of both pro- and anti-inflammatory interleukins, reflecting dynamic inflammatory response. To conclude, our findings provide new insights about the time-dependent DAMP activity in a large animal model of ischemic stroke, highlighting the simultaneous occurrence of an ongoing inflammatory response and the possible initiation of vascular remodeling as early as one week after stroke onset.